Diabeł - Zulawski, Andrzej; Jaroszewicz, Andrzej; Pszoniak, Wojciech; Teleszynski, Leszek; Miefiedow, Bożena
Formerly banned in Poland, Zulawski's second feature is set during the bloody Prussian invasion of Poland where a Satanic figure in black (Wojciech Pszoniak) frees a Jakub (Leszek Teleszynski), imprisoned for conspiracy to murder the king, in return for a list of his fellow conspirators. Traveling across a snowy, fiery, hellish war-torn landscape with a hostage nun, and this diabolic figure in tow, Jakub finds his family, friends, and loves either dead, insane, or political turncoats. A sprawling epic at just over two hours (film-speed), filled with blood, sex, and hysteria, this film is vintage Zulawski. The overstated performances aren't so much overacting as embodying emotional states (including some familiar shamanistic gyrating on the part of more then a few madwomen). Disguised as a period film about the Prussian invasion, critics have observed that it was actually Zulawki's commentary on the Poland he had grown up in. Consequently, the film was banned for seventeen years in its native country. [www.dvdbeaver.com]
Keywords: DVD-Video